Ensuring Equitable COVID-19 Vaccine Allocation in New Hampshire: The First Eight Months toward a New Era - Taylor D. Selembo; Elizabeth A. Talbot; Christophe T. Courtine; Elizabeth R. Daly; Torane W. Hull; Kirsten J. Durzy (Vaccines, 2022)
The global coronavirus disease 2019 (COVID-19) pandemic has been exacerbated by social vulnerabilities and racial disparities, resulting in disproportionate morbidity and mortality that require continued attention to strategies that ensure equitable vaccine allocation. The State of New Hampshire (NH) developed a transparent framework to guide COVID-19 vaccine allocation plans, of which one key component was the allocation of 10% of vaccine supply to disproportionately impacted and highly vulnerable populations, predominantly identified through a national vulnerability index. The process, operational approaches, ethical challenges, and unanticipated consequences resulted in many valuable lessons learned. Equitable allocation of this limited and critical pandemic countermeasure required public understanding and engagement, which was achieved through a publicly available framework that was flexible, resourced using public funds, and widely communicated. Broad partnerships were also critical to addressing disparities in the delivery of vaccine. The lessons learned and described here will facilitate more nimble and equitable jurisdictional responses in future public health emergencies.